Entrainment of Lemna CO(2) Output Through Phytochrome - Hillman, William S. (1971)
The entrainability of Lemna perpusilla CO(2) output by periodic 15 minute red (R) and far red (F) illuminations was tested in low nitrate medium. R every 8 hour, symbolized R/R/R, gives a flat output (no entrainment) as does F/F/F. However, R/—/— (R every 24 hour) entrains rapidly, and F/—/— does so as well, in a similar manner. The effects of R/R/— and F/F/— also resemble each other closely. Entrainment by R/F/F or R/R/F is rapid and indifferent to order of presentation, e.g., R/F/F and F/R/F lead to the same steady state. Typical phytochrome reversals occur, e.g., R,F/F/F holds output flat, while F,R/F/F entrains in the manner of R/F/F. Blue (B) light acts like R in schedules such as B/F/F but like F in schedules such as B/R/R. In all schedules studied, the zeitgeber (primary synchronizer) appears to be the sharpest transition from a low to a high level of far red-absorbing phytochrome that occurs with a 24-hr periodicity. Thus in entrainment, and by inference in photoperiodic timing, the level of far red-absorbing phytochrome at any time may be less significant than the succession of levels of which it is a part, a conclusion that implies the existence of a “scanning” mechanism that compares levels of far red-absorbing phytochrome at various times of day.